Literatur und Theologie im 18. Jahrhundert: Konfrontationen - Kontroversen - Konkurrenzen - Friedrich, Hans-Edwin; Haefs, Wilhelm; Soboth, Christian (Hallesche Beiträge zur europäischen Aufklärung, 2011)
"The relationship between theology and literature in the 18th century is not identical to the relationship between religion and literature or piety and literature, neither conceptually nor factually, neither historically nor systematically. On the whole the relationship can be described as unstable, and in detail as difficult and open. Church-historical differentiations in the religious spectrum of Judaism, Catholicism and - with historically appropriate internal differentiation - Protestantism connect the contributions throughout the literary-historical epochs from the Baroque period to Romanticism with the description and analysis of constellations and relationships of competition and supplementation, of confrontation and coexistence. For example, theology learned from literature how to captivate the congregation as an audience; literature - as sermon - wanted to take over the claim to meaning and orientation from theology."--Publisher's website